2021
DOI: 10.1002/ange.202112023
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabromo[36]octaphyrin: A Promising Precursor of Directly Fused Porphyrin(2.1.1.1) Dimer and meso‐α Fused N‐Confused Porphyrin Dimer

Abstract: 3,7,23,27‐Tetrabromo[36]octaphyrin 2 was synthesized as a novel octaphyrin bearing two meso‐free positions. Surprisingly, its ZnII and NiII complexation reactions produced a directly fused porphyrin(2.1.1.1) dimer 6, and a meso‐α fused N‐confused porphyrin (NCP) dimer 7, as the first example of NCP tape, respectively, via transannular C−C bond formation. While 6 exhibits a diatropic ring‐current effect owing to the global 36π Möbius aromaticity, 7 shows a paratropic ring‐current effect due to the global Hückel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Internally-bridged octaphyrin 1 was prepared from 5,10,15,25,30,35-hexakis(pentafluorophenyl)octaphyrin (i. e., meso-free octaphyrin) in two steps. [6,8] We initially envisioned that Ni II metalation of 1 may lead to meso-meso linked porphyrin dimer 2Ni. According to the DFT calculations, the formation of 2Ni is thermodynamically more favorable as compared with the case of 2Zn (See the Supporting Information, SI).…”
Section: Resultsmentioning
confidence: 99%
“…Internally-bridged octaphyrin 1 was prepared from 5,10,15,25,30,35-hexakis(pentafluorophenyl)octaphyrin (i. e., meso-free octaphyrin) in two steps. [6,8] We initially envisioned that Ni II metalation of 1 may lead to meso-meso linked porphyrin dimer 2Ni. According to the DFT calculations, the formation of 2Ni is thermodynamically more favorable as compared with the case of 2Zn (See the Supporting Information, SI).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme 1, we employed a [2 + 2 + 2 + 2]-type cross-condensation reaction for synthesis of octaphyrin bearing two Ni II porphyrins, which was used in our recent synthesis of tetrabromo[36]octaphyrin 13. [5] As our first attempt, acidcatalyzed cross-condensation of dipyrromethane dicarbinol 6 with meso-porphyrinyldipyrromethane 8 [4a] was examined under usual acid-catalyzed conditions. After oxidation, however, singly-linked porphyrin-[36]octaphyrin hybrid trimer 9 was not detected.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we examined Zn II metalation of 10, since tetrabromooctaphyrin 13 underwent spontaneous transannular meso-meso bond formation upon Zn II metalation to give Möbius aromatic bis-Zn II tetrabromo[36]octaphyrin 14. [5] Indeed, metal- [36]octaphyrin segment takes on a twisted structure with a dihedral angle of 88.5(7)°with respect to the Ni II porphyrin (Figure 2). [9] Importantly, in the 1 H NMR spectrum, the signals due to the β-protons of the [36]octaphyrin segment are observed at 8.27, 7.47, 7.31, 7.13, and 6.97 ppm, indicating a clear diatropic ring current.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, we found that 3,7,23,27-tetrabromo[36]octaphyrin was synthesized by using 3,7-dibromodipyrromethane dicarbinol 6 with dipyrromethane in the [2 + 2 + 2 + 2] manner with a quite suppressed formation of [2 + 2] product (i. e. 3,7-dibromoporphyrin). [11] Then, we aimed at the [2 + 3 + 2 + 3] type synthesis of tetrabromodecaphyrin by cross-condensation of tripyrrane 7 with dibromodipyrromethane dicarbinol 6 (Scheme 1). [12] After some screening, we found that p-toluenesulfonic Br 4 [M-H] À : 2422.8195), respectively.…”
Section: Resultsmentioning
confidence: 99%